Nanofluidics : nanoscience and nanotechnology - Edel, Joshua B.; De Mello, Andrew (RSC Publishing, 2009)
In his now celebrated lecture at the 1959 meeting of the American Physical Society, Richard Feynman pondered the potential of miniaturization in the physical sciences. His vision, based on known technology, examined the limits set by physical principles and proposed a variety of new nano-tools including the concept of ""atom-by-atom"" fabrication. In the intervening decades, many of these predictions have become reality. In particular, the development and application of nanofluidics is becoming a competitive and exciting field of research. These nanoscale analytical instruments employ micromac
Keywords: Nanoelectromechanical systems.; Fluidic devices.; Nanotechnology.; elektronické knihy; electronic books